Radiosensitization effects and ROS generation by high Z metallic nanoparticles on human colon carcinoma cell (HCT116) irradiated under 150 MeV proton beam - Raizulnasuha Abdul Rashid; Safri Zainal Abidin; Muhammad Afiq Khairil Anuar; Takahiro Tominaga; Hiroaki Akasaka; Ryohei Sasaki; Katahira Kie; Khairunisak Abdul Razak; Binh. T.T. Pham; Brian S. Hawkett; Mary-Ann Carmichael; Moshi Geso; et al. (Elsevier, 2019)
Radiosensitization effects caused by high atomic number (Z) metallic nanoparticles have been extensively explored with a wide range of X-ray based radiotherapy beams that seem to provide intriguing results for potential clinical applications. In this study, the radiobiological consequences of gold nanoparticles (AuNPs), superparamagnetic iron oxide nanoparticles (SPIONs), Platinum Nanodendrites (PtNDs) and Bismuth Oxide Nanorods (BiNRs) on Human Colon Carcinoma cells (HCT 116) irradiated with 150 MeV proton beams were investigated. Cell survival and reactive oxygen species (ROS) generation were measured. BiNRs demonstrates the highest sensitization enhancement ratio (SER) of 4.93 followed by PtNDs with SER value of 3.08. Meanwhile, AuNPs and SPIONs depict SER values around 2.64 and 1.95 respectively. The ROS generation corresponded to the level of radiosensitization with the highest ROS obtained for BiNRs and followed by PtNDs, AuNPs and SPIONs. In conclusion, high Z nanoparticles possess the potential to be clinically applied in proton beam therapy. Keywords: Gold nanoparticles, Superparamagnetic iron oxide nanoparticles, Platinum nanoparticles, Bismuth nanoparticles, Radiosensitization, Proton beam